Aggressive corrosion of steel by a thermophilic microbial consortium in the presence and absence of sand - Suarez, Erica; Lepkova, Katerina; Kinsella, Brian; Machuca Suarez, Laura (2019)
Microbiologically influenced corrosion of carbon steel by a thermophilic microbial consortium was investigated in the presence and absence of sand using surface analysis techniques and 16S rRNA gene sequencing. The activity of the consortium, involving methanogens, fermenting and sulphidogenic microorganisms, significantly increased average and localised corrosion regardless of the presence of sand deposit. Microbial metabolisms and syntrophic relationships of the consortium species contributing to accelerated corrosion were discussed. Electrochemical reactions are proposed based on the layers of corrosion products deposited on the metal surface. Differences in the microbial community composition and corrosion products stratification were identified between steel samples covered and uncovered with sand. This work is closely related to industrial applications highlighting the importance of conducting tests for under deposit corrosion incorporating microbial consortia isolated from the field environment. Otherwise, the severity of localised corrosion could be severely underestimated.